1984
DOI: 10.1073/pnas.81.2.512
|View full text |Cite
|
Sign up to set email alerts
|

Structural intermediates of deletion mutagenesis: a role for palindromic DNA.

Abstract: A model is presented for deletion mutations whose formation is mediated by palindromic and quasipalindromic DNA sequences. It proposes that the self-complementarity of palindromes allows the formation of DNA secondary structures that serve as deletion intermediates. The structures juxtapose the end points of the deletion and thus direct deletion specificity. While misaligned DNA intermediates that explain deletion termini occurring in repeated DNA sequences have been described, no explanations have been offere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(106 citation statements)
references
References 26 publications
6
100
0
Order By: Relevance
“…Such a process has been observed in other instances such as in deletion mutations at the hypoxanthine-guanine phosphoribosyl transferase locus in human T lymphocytes [30] or in deletions in the APRT gene of Chinese hamster ovary cells [31]. Glickman and Ripley [32] have proposed a model to explain deletion mutations in which palindromic and quasipalindromic DNA sequences enable the formation of secondary structures that are removed by deletion. In the human and mouse CRP sequences, the polypeptide LSPS(S/N)FSPPRPRTGL found in the linker portion of the human and mouse proteins is divergent from the three known CRPs.…”
Section: Discussionmentioning
confidence: 87%
“…Such a process has been observed in other instances such as in deletion mutations at the hypoxanthine-guanine phosphoribosyl transferase locus in human T lymphocytes [30] or in deletions in the APRT gene of Chinese hamster ovary cells [31]. Glickman and Ripley [32] have proposed a model to explain deletion mutations in which palindromic and quasipalindromic DNA sequences enable the formation of secondary structures that are removed by deletion. In the human and mouse CRP sequences, the polypeptide LSPS(S/N)FSPPRPRTGL found in the linker portion of the human and mouse proteins is divergent from the three known CRPs.…”
Section: Discussionmentioning
confidence: 87%
“…This observation was later found to hold for much larger spontaneous deletions (700-lOOO bp) in this same gene (30). Further analysis of such deletion data (31) showed that of those deletions which did not involve repeated DNA sequences, the majority contained palindromic or quasi-palindromic sequences capable of forming secondary structures that could juxtapose the end points of the deleted region and in this way direct the deletion specificity. Thus, in the latter case repeated DNA sequences are not required.…”
Section: Deletions Associated With Direct and Inverted Sequence Repeatsmentioning
confidence: 84%
“…Furthermore, the 65 bp sequence is part of exon 1 sequence in AM gene and unlikely to be deleted by alternative splicing events. Mechanisms accounting for the ability of a polymerase copying a template to skip a region and then resume faithful transcription of the remainder of the sequence have been proposed by others to explain internal deletions occuring during DNA synthesis by DNA polymerase (Glickman and Ripley, 1984;Cariello et al, 1991;Odelberg et al, 1995;Canceill and Ehrlich, 1996). In all cases, these models require that the deleted sequence contains a region of stable secondary structure.…”
Section: Discussionmentioning
confidence: 99%